2015
DOI: 10.1177/0885328215569892
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of biocompatibility of Ti–Mo–Sn–Zr superelastic alloy

Abstract: Shape memory alloys (SMAs) including superelastic alloys have unique properties such as shape memory and superelasticity, thus they are recognized as very useful biomaterials. These properties are very advantageous for medical use, and actually the SMA wires have been widely used in medical field. However, biocompatibility of nickel-titanium (Ni-Ti) alloy, which is the only practical SMA at present, has been questioned because of its high nickel content. The aim of this study was to evaluate the biocompatibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…For live cell imaging, fluorescein diacetate staining assay was performed as described previously [ 40 ]. The cells were incubated at 37 °C in an atmosphere of 5% CO 2 and examined on days 0 and 7 during the above-described neuritogenesis assay.…”
Section: Methodsmentioning
confidence: 99%
“…For live cell imaging, fluorescein diacetate staining assay was performed as described previously [ 40 ]. The cells were incubated at 37 °C in an atmosphere of 5% CO 2 and examined on days 0 and 7 during the above-described neuritogenesis assay.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we have focused on Zr addition to TiMo-Sn alloy as a quaternary additional element in order to solve these problems. In our previous research, it was reported that the biocompatibility of a Ti-3Mo-6Sn-5.2Zr alloy is comparable to the pure Ti [15]. In addition, it was also reported that Zr addition to Ti-Mo-Sn alloy decreases the martensitic transformation temperature by 42 K / mol%Zr with small change of the lattice deformation strain [16].…”
Section: Introductionmentioning
confidence: 93%
“…,Ti Ta 基 3 6) ,Ti Mo 基 7 10) 形状 記憶合金といった多くの合金が研究されている.しかし, 17) .さらに,Ti 3Mo 6Sn 5Zr(mol)合金では,時効温 度 に よ り 析 出 a 相 の 形 状 が 変 化 す る こ と も 報 告 し て い…”
Section: 緒 言unclassified